Lawn irrigation with domestic wastewater by subsurface drip or sprinkling - Mendonça, Rafael Barcelos [UNESP]; Bôas, Roberto Lyra Villas [UNESP]; de Godoy, Leandro José Grava [UNESP]; de Sousa, Renan Lima [UNESP] (FapUNIFESP (SciELO), 2020)
To maintain the quality of a lawn and allow it to perform its functions (esthetics, enhancement of property, reduction of air temperature, etc.) efficient use of irrigation and adequate fertilization are necessary. The use of wastewater from sewage treatment, which has a nutrient load, in irrigation, can be an alternative especially if applied via subsurface, to reduce contamination risks. This study was conducted to examine the development and quality of an ornamental lawn of Zoysia japonica Steud (zoysiagrass) irrigated with wastewater depths, by two methods. The experiment was carried out in Botucatu-SP, Brazil, during winter and spring (June to December 2016). The treatments consisted of two irrigation methods (sprinkling and subsurface drip) and four domesticwastewater irrigation depths (50%, 100%, 150% and 200% of the average daily evapotranspiration) plus control, where treated water was supplied by the Basic Sanitation Company of São Paulo State (Sabesp) of Botucatu, SP, Brazil, replacing 100% of average daily evapotranspiration. The following characteristics were studied: clipping dry matter weight, relative chlorophyll content, lawn height, total coliforms and Escherichia coli in the plant tissue and nutrient concentration in the leaves. Subsurface drip irrigation with wastewater, using an irrigation depth of 100% of the average evapotranspiration, allowed an adequate development of the zoysiagrass lawn by maintaining its quality, without contamination by total coliforms or Escherichia coli.
Irrigação em gramado com água residuária doméstica por gotejamento subsuperficial ou aspersão
Keywords: coliforms; fertigation; sewage treatment; Zoysia spp.